Plan estratégico de marketing para el posicionamiento de la marca ―marshell‖ productora de quesos del cantón Pillaro provincia de Tungurahua en el año 2014 - Caguana Guerra, Silvia Janeth (2016)
The project presented had as main objective to establish a strategic marketing plan in order to get "Marshell" position your brand. The development of a strategic marketing plan for microenterprise cheese comes in response to the constant need to embrace market segment. Definitely, factors such as planning, optimization, contributing decisively to achieve success in business is provided to change a full commitment to achieve the proposed challenges is meeting objectives and strategies. For the development of the Strategic Marketing Plan has made the collection of the information available to microenterprises, with respect to the essential characteristics of organization and its history in the financial field. the survey technique was used in this study using the questionnaire tool also inductive, deductive, statistical methods to obtain factual information and demonstrate that the creation of strategic marketing plan is necessary was used. It is very beneficial to include a strategic marketing plan to position the brand as it contributes to the obvious need for microenterprise in order to expand their market further concluded that the attributes such as price, quality standards, and technology used are important for customers also financial indices such as the various evaluation criteria indicate that the project is viable, moneymaking and therefore should be launched.